Variation of the characteristics of deltaic and stream bed deposits in laboratory studies - Reid, Thomas A., author; Brooks, Royal Harvard, author; Simons, Daryl B., author; Colorado State University, publisher (Colorado State University. Libraries, 1967)
This paper discusses the major processes that influence the distribution and characteristics of sedimentary deposits in deltaic systems (stream channel and delta). The distributions of the sediment sizes in the sedimentary deposits in several laboratory deltaic systems formed under steady-state conditions were determined. Statistical moments of the sediment size distribution were calculated and some explanations of their characteristics are given. Two size ranges of cohesionless sediments were use, along with several water discharges. The laboratory deltas were characterized by the classical top-, fore-, and bottom-set beds. Two- and three-dimensional deltas were analyzed and the relationships between the two are discussed. This paper should be of particular interest to the hydrologist, hydraulic engineer and sedimentologist whose interests include flow conditions that can be associated with a sedimentary deposit, rate of depositions in reservoirs, water resources development and sediment yield from rivers and river systems.
CER 67-68TAR-RHB-DBS34.
1967.
Keywords: Sedimentation and deposition